The Distributional Effects of Uniform Air Pollution Policy in the United States - Gianessi, Leonard P.; Peskin, Henry M.; Wolff, Edward (Quarterly Journal of Economics, 1979)
Introduction, 281.—Methods of analysis, 282.—Results, 287.—The distribution of net benefits, 293.—Policy implications and conclusions, 298.